FORMING THE UNITY OF THE INDIVIDUAL AND COLLECTIVE EXPERIENCE IN THE PROCESS OF SOCIALIZATION - Zakharash Т.B. (Pedagogy of Higher and Secondary Education, 2004)
The article deals with the main constituents of socializing process. Special attention is given to the necessity of combiningpositive individual and collective experience